Existence of nonnegative solutions for parabolic problem on Dirichlet forms. Issue 5 (4th April 2019) - Kenzizi, Tarek
ABSTRACT: In this work, we investigate perturbed parabolic problem on measure spaces. For strongly local Dirichlet form, we obtain some results on existence and uniqueness of nonnegative solution. We also presented some examples as an applications.